Science Motivation Profile of Students on the Concept of Particle Dynamics Topic - Hartini Hartini; Muhammad Syaipul Hayat; Nur Khoiri (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
Science education is something that is very crucial in forming an intelligent and creative generation. Science learning needs to be developed so that it can facilitate students in developing scientific thinking skills and motivation in studying science. This research aims to determine the Science Motivation profile students on the concept of particle dynamics. The research was conducted on class XI students of SMA Negeri 2 Boyolali. Samples were taken from class XI students totaling 67 male and female students. The data collection method used was the use of a Science Motivation questionnaire. The questionnaire data was tabulated using Excel and then the percentage was calculated. Based on analysis of the results of the student science motivation questionnaire, it shows that the science motivation of students at SMA Negeri 2 Boyolali is 79,85. Meanwhile, in terms of each indicator, it is as follows: the intrinsic motivation and personal relevance indicator is 78.45 (medium criteria), the packaging assessment indicator is 78.63 (medium criteria), the career self-determination indicator is 79,52 (medium criteria), career motivation indicator 82.69 (medium criteria) and class motivation indicator 84.18 (medium criteria).